2023
DOI: 10.1002/csc2.21112
|View full text |Cite
|
Sign up to set email alerts
|

Gendered sweetpotato trait preferences and implications for improved variety acceptance in Uganda

Chalmers K. Mulwa,
Hugo Campos,
Irene Bayiyana
et al.

Abstract: The principal selection objective in crop breeding has for a long time been driven by agronomic gains like yield maximization and climate resilience. Nevertheless, the continued low adoption of new varieties and documented gender technology adoption gap has triggered re‐thinking of this strategy, with end‐user acceptability of released varieties a key strategy in breeding objectives. Using a mixed methods approach with a survey of 122 producers and focus group discussions with 200 male and female producers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…In Namirimu et al (2024), a quantitative survey conducted found farmers' preferences varied by education level, age, and whether local or improved varieties were grown, but not by gender. In contrast, a study by Mulwa et al (2024) used a mixed quantitative and qualitative methods approach and found significant gender differences in preferences using both methods.…”
Section: Crop Sciencementioning
confidence: 93%
“…In Namirimu et al (2024), a quantitative survey conducted found farmers' preferences varied by education level, age, and whether local or improved varieties were grown, but not by gender. In contrast, a study by Mulwa et al (2024) used a mixed quantitative and qualitative methods approach and found significant gender differences in preferences using both methods.…”
Section: Crop Sciencementioning
confidence: 93%
“…Ssali et al (2023) found that women have a strong preference for sweetpotato quality traits such as mealiness, sweetness, and firmness. Mulwa et al (2023) similarly found that women prefer sweetpotato quality traits namely taste, high dry matter, and vitamin A, while men preferred agronomic traits including yield and early maturity. Mudege et al (2021), on the other hand, find, in the case of potatoes, that women preferred taste and tuber size.…”
Section: Introductionmentioning
confidence: 94%
“…Most farmers will therefore choose to grow a new variety if it has a preferred set or combination of desired traits or offers greater benefits than other existing varieties (Acheampong, 2015). However, this line of argument stems from neoclassical economic theory which has been the dominant theory used to examine the drivers of choice of crop varietal traits (Acevedo et al, 2020; Mulwa et al, 2023; Sanya et al, 2020; Thiele et al, 2021). The theory is premised on the assumption that choice actors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, this context is changing, and the breeder is no longer regarded as the sole decision maker and ‘artist’ in crop breeding 9 . A more holistic food system approach with attention to food democratisation of decision making regarding crop characteristics, informed by gender, social difference and place, are beginning to inform breeding programmes 4,5,10‐15 . Moreover, these initiatives require concerted, cross‐disciplinary effort for the re‐conceptualisation of technological research due to the very nature of the problems they aim to address – in this case to create new varieties based on diverse and varied interests within the food system in a just and equitable way 16 .…”
Section: Introductionmentioning
confidence: 99%